Numerical investigation of novel switchable microwave band-stop to bandpass filters - Adoum, B.A. (IEEE Computer Society, 2014)
Electronically switchable microwave filters are significant in increasing the capability of wireless communication and cognitive radios which is making them highly considerable for research and development. This paper describes and delves into the design of novel microwave switchable band-stop to bandpass filters. The filter is composed of stepped impedance resonators and can be switched to exhibit either band-stop or bandpass response. Switching was achieved by turning 'ON' and 'OFF' the PIN diodes switches incorporated into the filter structure. The switchable filter has been investigated numerically. The filter exhibits high stopband attenuation in the bandstop mode of operation and exhibits passband insertion loss around 7 dB in the bandpass mode of operation. This filter can be a promising option for maintaining or improving the current capability of wireless communication. Â© 2014 IEEE.